2017
DOI: 10.1080/13527258.2017.1341946
|View full text |Cite
|
Sign up to set email alerts
|

With New Eyes I See: embodiment, empathy and silence in digital heritage interpretation

Abstract: With New Eyes I See (WNEIS) was an immersive and itinerant digital heritage encounter exploring the exploitation of empathy made possible in such emergent formats. Located 'in the wild' , and timed to coincide with the 2014 Centenary of the First World War, WNEIS transformed Cardiff's civic centre as previously inaccessible stories and archival materials were projected onto, and playfully manipulated by, buildings and the natural environment. The research that underpinned the project unearthed a hitherto untol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…The detailed findings from the research have been presented elsewhere [13], but to summarise, we found that this project encouraged paricipants to perform their 'visitaion' to this heritage encounter very differently to that of a typical museum visit. The approach necessarily increased the sociality of the encounter and heightened paricipants' senses ofand desire for -agency.…”
Section: Overview: With New Eyes I See (Wneis)mentioning
confidence: 78%
See 4 more Smart Citations
“…The detailed findings from the research have been presented elsewhere [13], but to summarise, we found that this project encouraged paricipants to perform their 'visitaion' to this heritage encounter very differently to that of a typical museum visit. The approach necessarily increased the sociality of the encounter and heightened paricipants' senses ofand desire for -agency.…”
Section: Overview: With New Eyes I See (Wneis)mentioning
confidence: 78%
“…We wanted to make room for the varied potenials and limitaions of these digital heritage encounters to emerge in peoples' responses in ways that felt authenic, that were unpredictable to us, and that revealed the ways our resources did (or did not) come together to consitute a 'mulimodal whole' [36] with a 'mulimodal grammar' [36] that was ulimately producive for our paricipants. Following other scholars within the field of digital cultural heritage [5,6,9,8,13] we have found mulimodality a useful theoreical framework for exploring these cases, recognising as it does the importance of 'fine-grained detail of form and meaning' [36] and offering methodological prompts. This framework reminds us to pay atenion not only to textual and linguisic resources, but also to spaial, visual, aural and embodied aspects of interacion and environments [37].…”
Section: Talking About 'Experience'mentioning
confidence: 93%
See 3 more Smart Citations